ANALISIS TRANSFARANSI, AKUNTABILITAS DAN RESPONSIBILITAS DALAM PENGELOLAAN KEUANGAN DANA DESA: (Studi Pada Desa Penegah Kecamatan Pelawan Kabupaten Sarolangun tahun 2018-2020) - Yuli Sartika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
One of effect from national development priority agenda in government President Jokowi is issuance of Law No. 6/2014 on Villages, which states that the government will develop Indonesia from the periphery by strengthening regions and villages. The village government is expected to be able to manage it’s territory independently, including the management of assets, finances and village income so that it can improve the quality of life in the village and the welfare of the community. The purpose of this study was to find out the impplementation, problems and community responses about transparency, accountability and responsibility in managing village funds. This study uses descriptive qualitative methods. The data collection techniques used were observation, interview and documentation. The results of this study regarding the management of village funds in the Village of penegah in transparency, accountability and responsibility is good enough, although there are still some obstacles in their application in the field and the use of responsibility is not optimal.